Friction stir welding of dissimilar alloys and materials - Kumar, Nilesh, 1982-; Yuan, Wei; Mishra, Rajiv S. (Friction stir welding and processing book series., 2015)
This book will summarize research work carried out so far on dissimilar metallic material welding using friction stir welding (FSW). Joining of dissimilar alloys and materials are needed in many engineering systems and is considered quite challenging. Research in this area has shown significant benefit in terms of ease of processing, material mixing, and superior mechanical properties such as joint efficiencies. A summary of these results will be discussed along with potential guidelines for designers.